Green technologies in food production and processing - Arcand, Yves; Boye, Joyce I. (Food engineering series, 2012)
Examining the full cycle from farm to fork, this book reviews the current status of green processing in the agriculture and agri-food sector, and provides strategies for enhancing the use of environmentally-friendly technologies for production and processing